Are Russian Wheat Exporters Able to Price Discriminate? Empirical Evidence from the Last Decade. (24th January 2013) - Pall, Zsombor; Perekhozhuk, Oleksandr; Teuber, Ramona; Glauben, Thomas
Abstract: Significant changes have taken place in the world wheat market in the last decade. Russia, a former net wheat importer, has become a leading exporter with a world market share of 11.2% in 2009. This increasing importance and the discussion about the establishment of a grain‐OPEC consisting of Ukraine, Kazakhstan and Russia has raised the issue of pricing behaviour of Russian wheat exporters. Although there are several studies on the pricing behaviour of Canadian and US wheat exporters, there is none so far for Russian wheat exporters. This study provides a quantitative analysis of the pricing behaviour of Russian wheat exporters, explicitly taking account of the export tax imposed between 2007 and 2008. We employ a pricing‐to‐market (PTM) model on quarterly Russian wheat‐export data, covering the period from 2002 to 2010 and 25 export destinations. Our findings indicate that (i) Russian wheat exporters exercised PTM in only a few importing countries over the whole time period, and (ii) PTM behaviour was more pronounced in the aftermath of the export tax period (i.e. 2008–2010) than before.